Context adaptation of the communication stack - Mocito, José; Rosa, Liliana; Almeida, Nuno; Miranda, Hugo; Rodrigues, Luís; Lopes, Antónia (International journal of parallel, emergent and distributed systems, 2006)
This paper presents a middleware framework to support the development of context-aware adaptive communication protocols stacks. The protocol stacks can be reconfigured according not only to the local context, but also to the context of the remaining remote participants. The context information and the current node configuration feed a Markov decision process that is used to derive the appropriate reconfigurations. The advantages of the framework are illustrated using the concrete example of an adaptive group communication protocol. An experimental validation has been performed using a distributed chat application that can be executed in both fixed PCs and mobile devices.